Rights and Obligations of Husbands to Wife According to Law No. 1 of 1974 Article 34 and Islamic Law - Fathoni, M Insan; Wanti, Siti (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2024)
The differences in the concepts of rights and responsibilities outlined in Article 34 of Law No. 1 of 1974 and Islamic law create challenges for Indonesian society, especially regarding the roles of husbands and wives within a marriage. This study aims to explore these rights and obligations, comparing how they are defined in both legal frameworks and identifying their similarities and differences. This research is a library-based study using a comparative approach to analyze both perspectives. The findings show that, at their core, both systems prioritize family well-being and harmony. Both emphasize a husband’s duty to provide financial support and protection for his wife. However, the key difference lies in how these responsibilities are implemented and the legal foundations behind them. Islamic law places a strong emphasis on a wife’s obedience to her husband in matters that align with religious and moral principles (ma’ruf), while the law provides more detailed guidelines on the husband's duty to treat his wife well, both physically and emotionally. Ultimately, the rights and responsibilities of a husband toward his wife, as outlined in Article 34 of Law No. 1 of 1974 and Islamic law, center around financial support, protection, and family leadership. To maintain a harmonious household, a husband must understand and fulfill these responsibilities fairly, in accordance with both legal and religious principles.